The Past Before Us: A Brief History of Tongan Kava - Tecun, Arcia; Reeves, Robert; Wolfgramm, Marlena (Waka Kuaka, 2020)
This article examines deep and contemporary history through analysis of the Tongan kava origin story, a kava chant, the rise of the kalapu ‘kava club’ in the twentieth century and the growing expansion of contemporary kava. It is argued that a key function of past and present kava practices is a ritual liminality of noa ‘neutralisation of protective restrictions’ that results from mediating mana ‘potency, honour’ and tapu ‘protective restrictions, set apart’. This is supported through ethnohistorical literature, song lyrics and ethnographic data. While the expressions, purpose, material and uses of kava evolve and change throughout time and space, from the titular ceremonies to the social rituals, they are connected through contextually specific mediations that establish noa. The kava origin story indicates a performance of mediations between ancient power relations, while the kava chant describes material culture alongside the establishment of the ritualised chiefly kava ceremony. Kalapu and the expanding contemporary kava practices today maintain connections to past practices while adapting to current circumstances such as global Tongan mobility and cultural diversity.